1997
DOI: 10.1161/01.hyp.29.1.514
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile Compression of the Rostral Ventrolateral Medulla in Hypertension

Abstract: The rostra1 ventrolateral medulla (RVLM) has been known to be a major regulating center of sympathetic and cardrovascular acttvtttes An assoctatton between essential hypertension and neurovascular compressron of the RVLM has been reported m clmrcal observattons, mcludmg magnetic resonance tmagmg (MRI) studies To reconfirm this relattonshtp, we performed MRI usmg a high-resolutton 5 12X512 matrix m pattents wtth essential and secondary hypertenston and m normotensrve SubJeCtS The duratton of hypertension and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
52
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 19 publications
4
52
0
3
Order By: Relevance
“…[4][5][6][7][8][9][10] Using MRI, we found that the incidence of NVC of the RVLM in patients with EH was significantly higher than that in patients with secondary hypertension or in normotensive subjects, although the stage of hypertension did not differ significantly between the two hypertension groups. 11,12 We and others have reported that hypertensive patients show increased plasma levels of NE. 15,16 Therefore, it is assumed that NVC of the RVLM may be, at least in part, causally related to EH.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10] Using MRI, we found that the incidence of NVC of the RVLM in patients with EH was significantly higher than that in patients with secondary hypertension or in normotensive subjects, although the stage of hypertension did not differ significantly between the two hypertension groups. 11,12 We and others have reported that hypertensive patients show increased plasma levels of NE. 15,16 Therefore, it is assumed that NVC of the RVLM may be, at least in part, causally related to EH.…”
Section: Discussionmentioning
confidence: 93%
“…[4][5][6][7][8][9][10] We have reported that magnetic resonance imaging (MRI) with a high-resolution matrix revealed a significantly higher incidence of NVC of the RVLM in EH patients as compared with those with secondary hypertension or normotensive patients, although the degree of organ damage from hypertension was not significantly different between the two groups of hypertensive patients. 11,12 Jannetta et al 13,14 and we 15 have reported that microvascular decompression (MVD) of the RVLM decreases blood pressure (BP) in hypertensive patients with NVC of the RVLM. Therefore, it is assumed that MVD of the RVLM could be a useful therapeutic strategy to reduce BP in these patients.…”
Section: Introductionmentioning
confidence: 92%
“…However, our previous study in rats revealed that BP elevation by pulsatile compression of RVLM becomes more marked in a pressure-dependent manner. 15 Therefore, we cannot rule out the possibility that a decrease in arterial stimulation of RVLM by BP reduction led to a further reduction of BP. At present, there is an ongoing clinical study designed to compare the pressure-lowering effects of L-type calcium antagonists, which do not have sympatholytic effects, in NVC+ and NVC-patients.…”
Section: Discussionmentioning
confidence: 96%
“…5,6 After the initial report by Jannetta and Gendell in 1978, 7 several clinical studies have suggested an association between neurovascular contact (NVC) of RVLM and essential hypertension (EH). [8][9][10][11][12][13][14][15] Jannetta et al 16,17 have reported that MVD of RVLM decreases blood pressure (BP) in hypertensive patients with NVC of RVLM. MVD of RVLM could be a useful therapeutic strategy to reduce BP in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 A further support to the so-called 'neurogenic hypothesis' of hypertension comes from the evidence of a close link between some hypertensive states and neurovascular compression of the rostral ventrolateral medulla, that is, an area of the central nervous system with an important efferent pathway of the sympathetic nervous system. [2][3][4][5] This association is strengthened by the evidence that in different experimental animal models electrical, chemical or mechanical stimulation of the ventricular medulla triggers a transient pressor response. [6][7] It is also strengthened by the finding that in subgroups of patients with severe and/or resistant hypertension microsurgical decompression at the level of the rostral ventrolateral medulla substantially improves blood pressure control, leading to a long-term blood pressure normalization in a not negligible number of patients.…”
mentioning
confidence: 99%